Pengaruh Pembelajaran Coding Berbasis STEM terhadap Kemampuan Mahasiswa dalam Mengajar saat Magang di Lembaga Educourse - Anindya Galuh Prabeswari; Mu'arifuddin Mu'arifuddin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the effect of STEM-based coding learning on students' teaching abilities during their internship program at the Educourse Institute. The background of this research is the importance of mastering technology in the learning process, especially in today's digital era. This study employed a quantitative method with an ex post facto approach. The sample consisted of 98 internship students selected through total sampling. The research instrument used was a closed-ended questionnaire with a Likert scale. The data analysis results showed that STEM-based coding learning had a positive and significant influence on students' teaching abilities. Students who participated in coding learning showed improvements in opening lessons, explaining materials, providing teaching variations, and managing classrooms effectively. Therefore, the integration of STEM-based learning, particularly coding, is essential to be implemented in higher education so that future educators possess skills relevant to modern teaching demands.